Canagliflozin and Stroke in Type 2 Diabetes Mellitus: Results From the Randomized CANVAS Program Trials. Issue 2 (February 2019) - Zhou, Zien; Lindley, Richard I.; Rådholm, Karin; Jenkins, Bronwyn; Watson, John; Perkovic, Vlado; Mahaffey, Kenneth W.; de Zeeuw, Dick; Fulcher, Greg; Shaw, Wayne; Oh, Richard; Desai, Mehul; et al.
Abstract : Background and Purpose—: This study reports the detailed effects of canagliflozin on stroke, stroke subtypes, and vascular outcomes in participants with and without cerebrovascular disease (stroke or transient ischemic attack) at baseline from the CANVAS (Canagliflozin Cardiovascular Assessment Study) Program. Methods—: The CANVAS Program, comprising 2 similarly designed and conducted clinical trials, randomly assigned 10 142 participants with type 2 diabetes mellitus and high cardiovascular risk to canagliflozin or placebo. Its primary outcome was a composite of major adverse cardiovascular events. The main outcome of interest for this report was fatal or nonfatal stroke. Additional exploratory outcomes were stroke subtypes and other vascular outcomes defined according to standard criteria. Results—: There were 1 958 (19%) participants with prior stroke or transient ischemic attack at baseline. These individuals were older, more frequently women, and had higher rates of heart failure, atrial fibrillation, and microvascular disease (all P <0.001) compared with those without such a history. There were 309 participants with stroke events during follow-up (123 had prior stroke or transient ischemic attack at baseline and 186 did not), at a rate of 7.93/1000 patient-years among those assigned canagliflozin and 9.62/1000 patient-years among placebo (hazard ratio, 0.87; 95% CI, 0.69–1.09). Analysis of stroke subtypes found no effect on ischemic stroke (n=253, hazard ratio, 0.95; 95% CI, 0.74–1.22), a significant reduction for hemorrhagic stroke (n=30, hazard ratio, 0.43; 95% CI, 0.20–0.89) and no effect on undetermined stroke (n=29, hazard ratio, 1.04; 95% CI, 0.48–2.22). Effects on other cardiovascular outcomes were comparable among participants with and without stroke or transient ischemic attack at baseline. Conclusions—: There were too few events in the CANVAS Program to separately define the effects of canagliflozin on stroke, but benefit is more likely than harm. The observed possible protective effect for hemorrhagic stroke was based on small numbers but warrants further investigation. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifiers: NCT01032629 and NCT01989754. Abstract : Supplemental Digital Content is available in the text.